An ankylosing spondylitis risk variant alters osteoclast differentiation. (19th September 2022) - Wu, Fangyi; Han, Xuling; Liu, Jing; Zhang, Zhenghua; Yan, Kexiang; Wang, Beilan; Yang, Lin; Zou, Hejian; Yang, Chengde; Huang, Wei; Jin, Li; Wang, Jiucun; et al.
Abstract: Objective: To explore whether the variants in non MHC proteasome gene are associated with AS and explain the role of the variant in the disease. Material and methods: Case-control analysis to identify AS predisposition genes; dual-luciferase reporter assay, immunoblot analysis and osteoclastogenesis assays to detect the function of the positive variant. Affected individuals were diagnosed according to the modified New York Criteria by at least two experienced rheumatologists, and rechecked by another rheumatologist. Results: The study included 1037 AS patients and 1014 no rheumatic and arthritis disease controls. The main age of AS onset is between 16 and 35 years old. HLA-B27-positive subjects comprised 90.0% of patients. A nonsynonymous SNP rs12717 in proteasome gene PSMB1 significantly associated with AS. Individuals with CC genotype had a higher onset risk compared with those with GG/GC genotypes (OR = 1.89, P  = 0.0047). We also discovered that PSMB1 regulates the receptor activator of nuclear factor-κB (RANK)/RANK ligand (RANKL) signalling pathway and the disease-associated variant PSMB1-Pro11 significantly inhibits RANKL-induced NF-κB pathway in osteoclast differentiation via the degradation of IKK-β compared with PSMB1-Ala11. RANKL induced osteoclast differentiation was significantly lower in primary monocyte osteoclast precursor from individuals with genotype PSMB1 31C/31C compared with individuals with genotype PSMB1 31G/31G . Conclusions: These results reveal a novel understanding of the bone formation and reabsorbing imbalance in AS. The new bone formation phenotype can be attributed to the inhibition of osteoclast differentiation by a more functional PSMB1 gene.